Effects of microwave processing conditions on microbial safety and antimicrobial proteins in bovine milk. Issue 3 (17th December 2019) - Thum, Caroline; Ozturk, Gulustan; McNabb, Warren C.; Roy, Nicole C.; Leite Nobrega de Moura Bell, Juliana Maria
Abstract: The simultaneous effects of microwave processing variables affecting the microbial quality and preservation of milk bioactive proteins were evaluated. Response surface methodology was used to investigate the individual and combined effects of ramp time (2.9–5.5 min), holding time (6.6–23.4 s), and final temperature (60–80°C) on the inactivation of two surrogates ( Staphylococcus aureus and Escherichia coli ) added to the milk and on the preservation of the main antimicrobial proteins present in milk (lysozyme, lactoferrin, lactoperoxidase, xanthine oxidase, and immunoglobulin G). Experimental conditions resulting in 5 log reduction of E.coli and S. aureus (75°C, ramp time of 4.10 min, and holding time of 20 s) were replicated in quintuplicate for validation of the observed effects. At this experimental condition, more than 95% of the naturally present antimicrobial proteins were inactivated. The inactivation of antimicrobial proteins observed in this study was similar to the ones observed for ultra‐high temperature milk. Practical applications: The current study demonstrates that microwave heating conditions leading to microbial safety (5 log reduction of surrogates) result in significant inactivation of bovine milk antimicrobial proteins (>95%), being similar to the ones observed for ultra‐high temperature milk.